A Systematic Review on Use of Medicinal Plants for Male Infertility Treatment - Nasibeh Roozbeh; Azam Amirian; Fatemeh Abdi; Simin Haghdoost (Tehran University of Medical Sciences, 2021)
Objective: Male infertility is involved in about half of the casess of infertility and the only sole reason for infertility in 20%-30% of the cases. Following the recent interest in the use of medicinal plants, scientists have sought to clarify their effects on male fertility. This review aimed to summarize the results of studies available to determine the effectiveness, safety and mechanism of herbal treatments in the improvement of male fertility. Materials and methods: Medline/PubMed, Scopus, Science Direct, and the Cochrane Central Register of Controlled Trials (Central) databases were searched for randomized controlled trials (RCTs) published during 2000-2020. Studies were only included if they adhered to the CONSORT checklist. The methodological quality of the selected studies was assessed using the Cochrane risk of bias tool. Results: Finally, 20 studies recruiting a total of 1519 individuals were reviewed. These studies compared the effects of eleven different medicinal plants, i.e. ginseng, saffron, Nigella sativa, palm pollen, ADOFON, TOPALAF, sesame, and Mucuna pruriens, on male fertility with those of placebo. All studies (except one) confirmed the beneficial effects of medicinal plants on the improvement of sperm and reproductive parameters and thus male infertility. Conclusion: The existing RCTs indicated the positive effects of medicinal plants on male fertility. Therefore, in order to develop a novel approach to the treatment of male infertility, further clinical trials are warranted to determine the maximum dosage and duration of treatment with herbal medicines and evaluate any potential side effects of such interventions.